1992
DOI: 10.1002/apmc.1992.051950116
|View full text |Cite
|
Sign up to set email alerts
|

DSC investigation on the thermal degradation of PVC in blends

Abstract: The thermal degradation of poly(viny1 chloride) (PVC) has been studied by differential scanning calorimetry (DSC). Due to crosslinking, the glass transition temperature (Tg) of PVC raises during the degradation. The thermal degradation of PVC has also been studied for heterogeneous 1: 1 (w/w) blends of PVC with polystyrene (PS), poly(styrene-co-acrylonitrile) (SAN), high-impact PS (poly(styrene-g-butadiene)) (HIPS) and poly(SAN-g-butadiene) (ABS). Tg of the PVC phase raises slower during degradation in the PVC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Improved stability of the blend is more noticeable when concentration of polysiloxane is at least 50%. 316 In earlier studies, 260 PS was also found to decrease PVC degradation but HIPS increased PVC degradation rate (see Figure 4.49 and Section 4.5.1.6). 319 Figure 4.58 shows the effect of addition of PS on thermal stability of PVC blend.…”
Section: Poly(n-vinyl-2-pyrrolidone) Pvpmentioning
confidence: 77%
“…Improved stability of the blend is more noticeable when concentration of polysiloxane is at least 50%. 316 In earlier studies, 260 PS was also found to decrease PVC degradation but HIPS increased PVC degradation rate (see Figure 4.49 and Section 4.5.1.6). 319 Figure 4.58 shows the effect of addition of PS on thermal stability of PVC blend.…”
Section: Poly(n-vinyl-2-pyrrolidone) Pvpmentioning
confidence: 77%
“…The type of interaction will depend on the degree of miscibility of the components, as well as on their ratio in the blend. 1,2,17 Therefore, the effect of certain polymer modifiers on the thermal stability of PVC can be different.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that, under degradation conditions, considerable interactions may occur between the components in the polymer blend and their degradation products. The type of interaction will depend on the degree of miscibility of the components, as well as on their ratio in the blend 1, 2, 17. Therefore, the effect of certain polymer modifiers on the thermal stability of PVC can be different.…”
Section: Introductionmentioning
confidence: 99%